PENERAPAN LOW PASS FILTER UNTUK MEMPERBAIKI HASIL ESTIMASI SUDUT PADA SISTEM RADIO TRACKING ROKET - Zain, Satria Gunawan; Susanto, Adhi; Widodo, Thomas Sri; Kliwati, Sri; Widada, Wahyu (BRIN Publishing, 2010)
Radio tracking system can be applied to track the position of a rocket and is potential to be developed to replace the GPS technology. This system is used to estimate the direction angle (azimuth and elevation) of transmitter source. In measurement and trial there are many noises that cause the results of angle estimation are not accurate. These noises can be obsreved from the value of the angle estimation varied for a fixed measurement point. This is caused by the interference on the received sinyal. This paper discusses the application of low pass filter to eliminate noises in the radio receiver system. Experiment results show that the variation of estimates angle becomes 1600 times smaller compared to the one without filter